2020
DOI: 10.3390/s21010202
|View full text |Cite
|
Sign up to set email alerts
|

Driver Identification System Using Normalized Electrocardiogram Based on Adaptive Threshold Filter for Intelligent Vehicles

Abstract: Driver-centered infotainment and telematics services are provided for intelligent vehicles that improve driver convenience. Driver-centered services are performed after identification, and a biometrics system using bio-signals is applied. The electrocardiogram (ECG) signal acquired in the driving environment needs to be normalized because the intensity of noise is strong because the driver’s motion artifact is included. Existing time, frequency, and phase normalization methods have a problem of distorting P, Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…A normalized electrocardiogram (ECG) based adaptive threshold filter approach was also presented, which measures the ECG while the subject is sitting, touching a slide, and after the subject has finished exercising. The results of the studies show that the suggested method increased average similarity when compared to results obtained without the normalization step [32].…”
Section: Driver Identity Recognitionmentioning
confidence: 92%
“…A normalized electrocardiogram (ECG) based adaptive threshold filter approach was also presented, which measures the ECG while the subject is sitting, touching a slide, and after the subject has finished exercising. The results of the studies show that the suggested method increased average similarity when compared to results obtained without the normalization step [32].…”
Section: Driver Identity Recognitionmentioning
confidence: 92%
“…e matching of motion trajectory is to use the Mahalanobis distance of the positioning position predicted in the filter by the detection result and tracking result to express its degree [14]. e equation is as follows:…”
Section: General Video Feature Extraction Methods Based On DLmentioning
confidence: 99%
“…The state of an object is to describe the trajectory state at a certain time in an 8-dimensional space. The matching of motion trajectory is to use the Mahalanobis distance of the positioning position predicted in the filter by the detection result and tracking result to express its degree [ 14 ]. The equation is as follows: y i is the predicted observation of the trajectory, d j is the result state of the j -th, and S i is the covariance matrix obtained through the filter.…”
Section: Construction and Application Analysis Of Moving Target Detec...mentioning
confidence: 99%
“…Choi et al [43] used a continuous firstorder regression analysis method to remove baseline wondering noise, maintaining morphological features and adjusting them to zero. In addition, a normalization study was conducted in which the morphological features of the ideal ECG cycle P, QRS Complexes, and T waves were clearly generated [44]. Rehman et al [45] confirmed the fiducial point segmentation method using the P, QRS Complexes, and T waves features of the ECG's one cycle with higher identification accuracy than the nonfiducial point segmentation method.…”
Section: Driver Identification System Usingmentioning
confidence: 99%